Isıl işlemin NiTi şekil hatırlamalı alaşımının (ŞHA) mikroyapısı, dönüşüm sıcaklığı ve termal çevirimi üzerine etkisi - Dağdelen, Fethi; Buytoz, Soner; Kök, Mediha; Ercan, Ercan (Erciyes Üniversitesi, 2015)
Hava atmosferinde 400- 700 0C aralığında ısıl işlem uygulanan, atomik konsantrasyonu Ni-45.16%Ti şekil hatırlamalı alaşımın termal stabilitesi(çevrim) ve aktivasyon enerjisi incelenmiştir. Thermal çevrim, düşük döünüşüm sıcaklığına meyilli ve R faz göstermemektedir. Ana numune ve ısıl işleme maruz bırakılmış numunelerin thermal stabilitesinin deneysel işlemler düştüğünü göstermiştir. Bu alaşımların aktivasyon enerjisi Diferansiyel taramalı kalorimetre (DSC) ile belirlenmiştir.Dönüşüm sıcaklıklarının (Ms, Mf, As ve Af) ve Kissinger ve Ozawa yöntemiyle ölçülen termal aktivasyon enerjilerinin, ısıl işlem ile arttığı görülmüştür.Bununla birlikte Vickers sertlik değerlerinin ise ısıl işlemle azaldığı görülmüştür.

The thermal stability (cycle) and activation energies of NiTi shape memory alloy (SMA), in Ni-45.16%Ti atomic consantration (SMA), which exposed to heat treatment in air in the temperature range 400-800 0C Ni-45.16%Ti has composition in atomic percent, was investigated that it was exposed to heat treatment in air in the temperature range 400-800 0C. The thermal cycles tend to lower the transformation characteristic temperature, and thermal cycles couldn’t display introduce R phase. Experimental results indicate that thermal stability of as-cast and exposed to heat treatedment samples were decreased. The thermal activation energies of these alloys also were determined by Differential Scanning Calorimeter (DSC). It was seen that both transformation temperature of samples (Ms, Mf, As and Af) and the thermal activation energies calculated byfor Ozowa and Kissinger methods of alloys increased with the heat treatment exposed to heat treatment were increased. However, it was determined that results of vickers hardness values measurement of these shape memory alloys were decreased with the heat treatment.
Heat treatment effects on thermal cycle,transition temperature and microstructure of NiTi shape memory alloy(SMA)